A high-strength fire-resistant gypsum mortar and preparation method thereof

By adding specific fillers and nanocellulose to the gypsum mortar to the modification treatment, the particle-sheet composite structure is formed, which solves the shortcomings of the existing gypsum mortar in terms of refraction resistance and strength, and achieves the effect of high-strength refraction resistance.

CN119100735BActive Publication Date: 2025-03-11JIANGYIN TIANBANG ENVIRONMENTAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411162689.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-23
Publication Date
2025-03-11
Estimated Expiration
2044-08-23

AI Technical Summary

Technical Problem

The existing gypsum mortar has shortcomings in terms of refraction resistance and strength, which is difficult to meet the demand for high-strength refractory materials in buildings.

Method used

By adding vitrified microbeads, polystyrene particles, redispersible latex powder and layered hydrotalcite to the gypsum mortar, and combining with the modification of nanocellulose, a particle-sheet composite structure is formed to improve the density, water absorption, water resistance and thermal conductivity of the mortar.

Benefits of technology

It significantly improves the refractory effect and strength of gypsum mortar, forms a good heat-insulating, refractory and flame-retardant structure, and enhances the combination effect of fillers and mortar substrates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005006890090000091
    Figure BDA0005006890090000091
  • Figure BDA0005006890090000101
    Figure BDA0005006890090000101
  • Figure BDA0005006890090000111
    Figure BDA0005006890090000111
Patent Text Reader

Abstract

The present application relates to the technical field of gypsum mortar, and specifically discloses a high-strength and fire-resistant gypsum mortar and a preparation method thereof. The high-strength and fire-resistant gypsum mortar comprises the following substances in parts by weight: 60-80 parts of gypsum; 20-30 parts of cement; 10-20 parts of aggregate; 5-10 parts of filler; 3-5 parts of admixture; the filler comprises vitrified microspheres, polystyrene particles and redispersible latex powder, and the filler also comprises layered hydrotalcite. The preparation method thereof is as follows: S1, raw material preparation; S2, mortar preparation. The gypsum mortar of the present application can be used in the construction industry, and it has the advantages of high strength, fire resistance and waterproofness; in addition, the preparation method of the present application has the advantages of simple operation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of mortar, and more specifically, to a high-strength and fire-resistant gypsum mortar and a preparation method thereof. Background Art

[0002] Gypsum mortar is a new type of building material, which is made of gypsum as the main raw material and mixed with an appropriate amount of inorganic fillers and additives. Gypsum mortar has the characteristics of good adhesion, fast hardening, high compressive strength, good water resistance, etc., so it has been widely used in the construction industry.

[0003] The combustion performance and fire resistance of building materials are very important for buildings to resist fire or prevent the spread of fire. Therefore, gypsum mortar needs to have better strength and better fire resistance. Summary of the invention

[0004] In order to improve the fire resistance and strength of gypsum mortar, the present application provides a high-strength fire-resistant gypsum mortar and a preparation method thereof, adopting the following technical scheme:

[0005] In a first aspect, the present application provides a high-strength fire-resistant gypsum mortar, comprising the following substances in parts by weight:

[0006] 60-80 parts of gypsum;

[0007] 20-30 parts of cement;

[0008] Aggregate 10-20 parts;

[0009] 5-10 parts of filler;

[0010] 3-5 parts of admixture;

[0011] The filler includes glass microspheres, polyphenyl particles and redispersible latex powder, and the filler also includes layered hydrotalcite.

[0012] By adopting the above technical solution, the addition of polystyrene particles can effectively improve the density, water absorption, water resistance and thermal conductivity of gypsum mortar, thereby improving the fire resistance of gypsum mortar. The unique hollow structure of vitrified microspheres will bypass the vitrified microspheres during heat transfer, thereby reducing the thermal conductivity of gypsum mortar and reducing the water absorption of gypsum mortar, so that gypsum mortar has better fire resistance and water resistance. The combination of polystyrene particles and vitrified microspheres can effectively give gypsum mortar excellent fire resistance, and can form a good grading effect, effectively improving the strength of gypsum mortar.

[0013] It is preferred to use redispersible latex powder as filler. The addition of redispersible latex powder can form a polymer film in the mortar to wrap the pore structure, which can further reduce the fire resistance of the mortar and the bonding effect of the components in the mortar.

[0014] Layered hydrotalcite is added to the filler. Since the layered hydrotalcite can adsorb polystyrene particles, the polystyrene particles can be partially loaded on the surface of the layered hydrotalcite. The layered hydrotalcite has good hydrophilicity, can reduce the agglomeration of polystyrene particles and improve the dispersion effect of polystyrene particles in the mortar, and can form a particle-lamellar composite structure, can form a good heat-insulating, fire-resistant and flame-retardant structure, which is beneficial to improve the strength and fire-resistant effect of the gypsum mortar.

[0015] Optionally, the layered hydrotalcite is a layered hydrotalcite modified by a modifier, and the modifier includes nanocellulose.

[0016] By adopting the above technical solution, it is preferred to use nanocellulose to modify the layered hydrotalcite. The layered hydrotalcite surface has more active groups, and the nanocellulose and the layered hydrotalcite can be combined through hydrogen bonds. The one-dimensional structure and the two-dimensional structure are stacked on each other to form a multilayer structure, which can further extend the heat transfer path, reduce the thermal conductivity of the mortar, improve the fire resistance of the mortar, and enhance the bonding effect of the filler and the mortar substrate. The introduction of nanocellulose can also increase the fiber structure in the mortar, enhance the bonding effect of the polystyrene particles and the layered hydrotalcite, and enable the mortar to obtain excellent fire resistance and strength.

[0017] Optionally, the nanocellulose includes modified nanocellulose modified with stearyl chloride.

[0018] By adopting the above technical solution, nanocellulose is modified by stearyl chloride, and stearyl chloride and nanocellulose are grafted through esterification reaction, so that an esterified outer layer is formed on the surface of nanocellulose. The esterified outer layer can swell and promote the occurrence of self-assembly, which can not only improve the binding effect between nanocellulose and layered hydrotalcite, but also improve the binding effect between nanocellulose and polystyrene particles, so that the layered hydrotalcite can fully disperse the polystyrene particles, so that the gypsum mortar obtains a uniform fire-resistant effect.

[0019] Optionally, the modified nanocellulose is prepared as follows: nanocellulose, N,N-dimethylacetamide and pyridine are mixed, stearoyl chloride is added, stirred to react to obtain a reaction product, the reaction product is dispersed in ethanol, centrifuged, the precipitate is retained, washed, and dried to obtain the modified nanocellulose.

[0020] Optionally, the nanocellulose further comprises grafted nanocellulose, on which cyclodextrin is grafted.

[0021] By adopting the above technical solution, cyclodextrin is grafted onto nanocellulose, and cyclodextrin can be intercalated into the interlayer structure of hydrotalcite, thereby improving the connection strength between nanocellulose and hydrotalcite. Since nanocellulose includes grafted nanocellulose and modified nanocellulose, entanglement can occur between fiber structures, so that nanocellulose can be connected to hydrotalcite by self-assembly and intercalation, thereby improving the connection strength between nanocellulose and hydrotalcite, and then improving the bonding strength between polyphenylene particles and hydrotalcite, that is, hydrotalcite can fully disperse polyphenylene particles.

[0022] Optionally, the polystyrene particles are loaded with waterproof powder, and the waterproof powder is silane-based polymer waterproof powder.

[0023] By adopting the above technical solution, polystyrene particles are used to load waterproof powder. The polymer waterproof powder can condense with the surface of cement particles to form chemical bonds, adsorb on the surface of cement particles, and form a hydrophobic layer on the surface of cement particles, thereby delaying the erosion of liquid water, improving the water resistance of mortar, and improving the bonding effect between polystyrene particles and cement, thereby improving the strength of gypsum mortar.

[0024] Optionally, the polystyrene particles are coated with redispersible latex powder.

[0025] By adopting the above technical scheme, the polystyrene particles are wrapped with redispersible latex powder, and a redispersible latex shell is formed outside the polystyrene particles, so that the polystyrene particles become hydrophilic, and the dispersion effect of the polystyrene particles in the gypsum mortar is improved. As the mixing time increases, the waterproof powder can be gradually released, further improving the bonding effect between the polystyrene particles and cement, and effectively improving the strength of the gypsum mortar.

[0026] Optionally, the polystyrene particles are prepared as follows: immersing the polystyrene particles in a waterproof powder finishing liquid, stirring and mixing, filtering, and drying to obtain loaded polystyrene particles, and spraying a redispersible latex liquid on the surface of the loaded polystyrene particles to obtain modified polystyrene particles.

[0027] Optionally, the admixture includes a water reducer and zinc borate, and the water reducer includes a polycarboxylate water reducer.

[0028] By adopting the above technical scheme, it is preferred to add a polycarboxylate water reducer to the mortar. The polycarboxylate water reducer has a certain air entraining effect, and the bubbles produced have a ball rolling and floating effect, which can effectively improve the uniformity of the dispersion of the filler in the gypsum mortar, so that the polystyrene particles and the vitrified microspheres can be evenly distributed in the gypsum mortar to play a fire-resistant effect. The addition of a water reducer can reduce the mixing water consumption in the mortar, reduce the pores formed by the evaporation of water inside the hardened body, thereby improving the strength of the gypsum mortar, and is conducive to forming a high-strength and fire-resistant gypsum mortar. Zinc borate is a mesh material that can produce viscosity after combustion, which can make the carbon layer produced by combustion more complete and dense, so as to achieve a better flame retardant effect. And zinc borate can cooperate with hydrotalcite, and zinc borate can assist hydrotalcite in forming a stable and thickened carbon layer, which can further improve the fire-resistant and flame-retardant effect of gypsum mortar.

[0029] In a second aspect, the present application provides a method for preparing high-strength refractory gypsum mortar, which adopts the following technical solution:

[0030] A method for preparing high-strength fire-resistant gypsum mortar comprises the following steps:

[0031] S1. Raw material preparation: Take gypsum, cement, filler, aggregate, admixture and water respectively by weight;

[0032] S2. Preparation of mortar: Stir and mix the filler, aggregate and admixture, add gypsum and cement and mix evenly, then add water and continue stirring to prepare gypsum mortar.

[0033] In summary, this application has the following beneficial effects:

[0034] 1. Since the present application adds layered hydrotalcite to the filler, the layered hydrotalcite can adsorb the polystyrene particles so that the polystyrene particles can be partially loaded on the surface of the layered hydrotalcite. The layered hydrotalcite has good hydrophilicity, can reduce the agglomeration of the polystyrene particles and improve the dispersion effect of the polystyrene particles in the mortar, and can form a particle-lamellar composite structure, which can form a good heat-insulating, fire-resistant and flame-retardant structure, which is beneficial to improve the strength and fire-resistant effect of the gypsum mortar.

[0035] 2. In the present application, nanocellulose is modified by stearoyl chloride, and stearoyl chloride and nanocellulose are grafted by esterification reaction, so that an esterified outer layer is formed on the surface of nanocellulose. The esterified outer layer can swell and promote the occurrence of self-assembly, which can not only improve the binding effect between nanocellulose and layered hydrotalcite, but also improve the binding effect between nanocellulose and polystyrene particles, so that the layered hydrotalcite can fully disperse the polystyrene particles, so that the gypsum mortar obtains a uniform fire-resistant effect.

[0036] 3. The present application utilizes polystyrene particles to load waterproof powder. The polymer waterproof powder can condense with the surface of cement particles to form chemical bonds, adsorb on the surface of cement particles, and form a hydrophobic layer on the surface of cement particles, thereby delaying the erosion of liquid water, improving the water resistance of the mortar, and being able to improve the bonding effect between polystyrene particles and cement, thereby improving the strength of the gypsum mortar. DETAILED DESCRIPTION

[0037] The present application is further described in detail below with reference to the embodiments.

[0038] KH550: analytically pure, McLean; polyvinyl alcohol: analytically pure, McLean; isobutyltriethoxysilane: analytically pure, McLean; stearoyl chloride: analytically pure, McLean; nanocellulose: analytically pure, 20-50nm.

[0039] Preparation Example

[0040] Waterproof powder preparation example

[0041] Preparation Example 1

[0042] Take equal masses of KH550, polyvinyl alcohol and isobutyltriethoxysilane, mix them to obtain a polymer solution, add an emulsifier to the polymer solution, the emulsifier addition amount is 20%, the emulsifier includes equal masses of Span-80 and OP-10, stir and mix to obtain an emulsion, add ultrafine calcium carbonate to the emulsion, the mass ratio of the emulsion to the ultrafine calcium carbonate is 1:1, stir, and fluidize and dry to obtain a waterproof powder.

[0043] Polyphenylene Particle Preparation Example

[0044] Preparation Example 2

[0045] The waterproof powder and polystyrene particles were mixed in a mass ratio of 1:2, dispersed in an aqueous solution containing a silane coupling agent KH550 (the content of KH550 was 10%), with a solid-liquid ratio of 1:10, ultrasonically dispersed, filtered, and dried to obtain polystyrene particles loaded with waterproof powder.

[0046] Preparation Example 3

[0047] Under the premise of tumbling the polystyrene particles loaded with waterproof powder, the redispersible latex liquid (mass fraction is 5%) is sprayed and dried to obtain the polystyrene particles wrapped with the redispersible latex powder.

[0048] Preparation Example of Layered Hydrotalcite

[0049] Preparation Example 4

[0050] The layered hydrotalcite was mixed with water to obtain a dispersion with a mass fraction of 10%. The nanocellulose was mixed with water to obtain a suspension with a mass fraction of 20%. The dispersion was added dropwise to the suspension, with a mass ratio of hydrotalcite to nanocellulose of 1:2, ultrasonically stirred for 2 hours, filtered, and dried to obtain a modified layered hydrotalcite.

[0051] Preparation Example 5

[0052] The layered hydrotalcite was mixed with water to obtain a dispersion with a mass fraction of 10%. The modified nanocellulose was mixed with water to obtain a suspension with a mass fraction of 20%. The dispersion was added dropwise to the suspension, with the mass ratio of hydrotalcite to modified nanocellulose being 1:2, ultrasonically stirred for 2 hours, filtered, and dried to obtain the modified layered hydrotalcite.

[0053] The modified nanocellulose was prepared as follows: 1 g of nanocellulose, 20 g of N,N-dimethylacetamide and 20 g of pyridine were mixed at 50°C, stearoyl chloride (the molar ratio of stearoyl chloride to nanocellulose was 3:1) was added, and the reaction was stirred for 4 h to obtain a reaction product, which was dispersed in ethanol, centrifuged, the precipitate was retained, washed, and dried to obtain modified nanocellulose.

[0054] Preparation Example 6

[0055] The layered hydrotalcite was mixed with water to obtain a dispersion with a mass fraction of 10%. The nanocellulose was mixed with water to obtain a suspension with a mass fraction of 20%. The dispersion was added dropwise to the suspension, with a mass ratio of hydrotalcite to nanocellulose of 1:2, ultrasonically stirred for 2 hours, filtered, and dried to obtain a modified layered hydrotalcite.

[0056] Nanocellulose includes modified nanocellulose and grafted nanocellulose in equal amounts.

[0057] The modified nanocellulose was prepared as follows: 1 g of nanocellulose, 20 g of N,N-dimethylacetamide and 20 g of pyridine were mixed at 50°C, stearoyl chloride (the molar ratio of stearoyl chloride to nanocellulose was 3:1) was added, and the reaction was stirred for 4 h to obtain a reaction product, which was dispersed in ethanol, centrifuged, the precipitate was retained, washed, and dried to obtain modified nanocellulose.

[0058] The preparation of grafted nanocellulose is as follows: weigh 7g of nanocellulose in a container, add 90mL of 1.5mol / L NaOH solution, stir at 50℃ for 2h, filter, wash until the pH value is neutral, and dry to obtain pretreated cellulose. Weigh 2g of pretreated cellulose in a container, add 50mL of deionized water to swell for 1h, then add 12mL of epichlorohydrin and 16mL of 30% NaOH solution, stir at 40℃ for 2.5h, filter, wash with deionized water until neutral, wash three times with 95% ethanol, filter, and dry to obtain epoxy cellulose. Take 1.152g of β-cyclodextrin, add 20mL of 30% NaOH solution, stir until β-cyclodextrin is dissolved, then add 1g of epoxy cellulose, react at 50℃ for 2h, filter, wash repeatedly with distilled water until the solution is neutral, dry, and grind into powder to obtain grafted cellulose.

[0059] Example

[0060] Examples 1-3

[0061] On the one hand, the present application provides a high-strength and fire-resistant gypsum mortar, including gypsum, cement, aggregate, filler and admixture, and the specific quality is shown in the table below.

[0062] The filler includes glass microspheres, polystyrene particles, redispersible latex powder and layered hydrotalcite in a mass ratio of 3:1:1:1.

[0063] The admixtures include polycarboxylic acid water reducer, zinc borate, hydroxypropyl methylcellulose ether and defoaming agent in a mass ratio of 2:0.5:0.5:0.5.

[0064] Aggregates include quartz sand.

[0065] Gypsum: Desulfurized gypsum, Shandong Guangyuan Chemical Co., Ltd., density 2.32g / cm 3 ; Cement: PO 42.5 grade, specific surface area 346m 2 / kg; Vitrified microspheres: expanded vitrified microspheres from Langfang Lvxiang Environmental Protection Technology Co., Ltd.; Polystyrene particles: made from discarded polystyrene boards after crushing, with a particle size of 2 to 4 mm and a bulk density of 18 kg / m 3 ; Redispersible latex powder: Hebei Chaoyan New Materials Technology Co., Ltd., average particle size is 80μm; layered hydrotalcite: Jiangsu Jufeng Chemical Technology Co., Ltd., industrial grade, aluminum-magnesium hydrotalcite; polycarboxylate water reducer: Sika 540P polycarboxylate water reducer; defoaming agent: Henan Kexing Water Treatment Materials Co., Ltd., kx-442 type.

[0066] On the other hand, the present application provides a method for preparing high-strength refractory gypsum mortar, comprising the following steps:

[0067] S1. Raw material preparation:

[0068] S11. Take gypsum, cement, filler, aggregate, admixture and water respectively according to weight, and the water-cement ratio is 0.45.

[0069] S12, dispersing polyphenyl particles and layered hydrotalcite in a tetrahydrofuran solution at a solid-to-liquid ratio of 2:10, stirring and mixing to obtain a mixture, mixing the mixture with ethanol at a volume ratio of 1:4, filtering, and drying to obtain a pretreated mixture;

[0070] S2. Preparation of mortar: Stir and mix the filler, aggregate and admixture, add gypsum and cement and mix evenly, then add water and continue stirring to prepare gypsum mortar.

[0071] Table 1 Composition of Examples 1-3

[0072]

[0073]

[0074] Example 4

[0075] The difference from Example 3 is that an equal mass of the layered hydrotalcite prepared in Preparation Example 4 is used to replace the layered hydrotalcite in Example 3 to prepare the gypsum mortar.

[0076] Example 5

[0077] The difference from Example 3 is that an equal mass of the layered hydrotalcite prepared in Preparation Example 5 is used to replace the layered hydrotalcite in Example 3 to prepare the gypsum mortar.

[0078] Example 6

[0079] The difference from Example 3 is that an equal mass of the layered hydrotalcite prepared in Preparation Example 6 is used to replace the layered hydrotalcite in Example 3 to prepare the gypsum mortar.

[0080] Example 7

[0081] The difference from Example 3 is that an equal mass of the modified polystyrene particles prepared in Preparation Example 2 is used to replace the polystyrene particles in Example 3 to prepare the gypsum mortar.

[0082] Example 8

[0083] The difference from Example 3 is that an equal mass of polystyrene particles coated with redispersible latex powder prepared in Preparation Example 3 are used to replace the polystyrene particles in Example 3 to prepare gypsum mortar.

[0084] Example 9

[0085] The difference from Example 6 is that an equal mass of polystyrene particles coated with redispersible latex powder prepared in Preparation Example 3 are used to replace the polystyrene particles in Example 3 to prepare gypsum mortar.

[0086] Comparative Example

[0087] Comparative Example 1

[0088] The difference between this comparative example and Example 3 is that no layered hydrotalcite is added in this comparative example.

[0089] Comparative Example 2

[0090] The difference between this comparative example and Example 3 is that no polystyrene particles are added in this comparative example.

[0091] Performance testing

[0092] (1) Fire resistance test: Test according to GB / T9978.1-2008 “Fire resistance test methods for building components Part 1: General requirements” and record the highest temperature rise of the non-fire side of the sample.

[0093] (2) Mechanical properties testing: "Gypsum-based self-leveling mortar" (JC / T 1023-2021) tests the mechanical properties of mortar.

[0094] Table 2 Performance test

[0095]

[0096]

[0097] In Examples 1-9, no flame lasting for 10 seconds or more appeared on the back-fired side of the test piece, no cracks penetrating into the test furnace appeared on the back-fired side, the cotton pad was not ignited, the test piece still maintained integrity, and the test was stopped.

[0098] Combining the performance test comparison in Table 2, we can find that:

[0099] 1. By comparing Examples 1-3 with Comparative Examples 1-2, it can be found that the fire-resistant effect and mechanical properties of the gypsum mortar prepared in Examples 1-3 are improved, which means that in the present application, layered hydrotalcite is added to the filler, and the layered hydrotalcite can be used to adsorb polystyrene particles, so that the polystyrene particles can be partially loaded on the surface of the layered hydrotalcite. The layered hydrotalcite has good hydrophilicity, can reduce the agglomeration of polystyrene particles and improve the dispersion effect of polystyrene particles in the mortar, and can form a particle-lamellar composite structure, which can form a good heat-insulating, fire-resistant and flame-retardant structure, which is beneficial to improve the strength and fire-resistant effect of the gypsum mortar. The introduction of polystyrene particles reduces the mechanical strength of the gypsum mortar, but can effectively improve the fire-resistant performance and lightness of the gypsum mortar, and improve the application performance of the gypsum mortar.

[0100] 2. By comparing Example 4 with Example 3, it can be found that the fire resistant effect and mechanical properties of the gypsum mortar prepared in Example 4 are improved, which shows that in the present application, nanocellulose and layered hydrotalcite can be combined through hydrogen bonds, and the one-dimensional structure and the two-dimensional structure are stacked on each other to form a multilayer structure, which can further extend the heat transfer path, reduce the thermal conductivity of the mortar, improve the fire resistant effect of the mortar, and enhance the bonding effect between the filler and the mortar substrate. The introduction of nanocellulose can also increase the fiber structure in the mortar, enhance the bonding effect between the polystyrene particles and the layered hydrotalcite, and enable the mortar to obtain excellent fire resistant effect and strength.

[0101] 3. By comparing Example 5 with Example 3, it can be found that the fire resistant effect and mechanical properties of the gypsum mortar prepared in Example 5 are improved, which indicates that in the present application, the nanocellulose is modified by stearyl chloride to form an esterified outer layer on the surface of the nanocellulose. When the layered hydrotalcite is mixed with polystyrene, the esterified outer layer can swell and promote the occurrence of self-assembly, which can not only improve the binding effect between the nanocellulose and the layered hydrotalcite, but also improve the binding effect between the nanocellulose and the polystyrene particles, so that the layered hydrotalcite can fully disperse the polystyrene particles, so that the gypsum mortar obtains a uniform fire resistant effect.

[0102] 4. By comparing Example 6 with Example 3, it can be found that the fire resistant effect and mechanical properties of the gypsum mortar prepared in Example 6 are improved, which shows that the combination of grafted nanocellulose and modified nanocellulose in the present application can cause entanglement between the fiber structures, so that the nanocellulose can be connected with the hydrotalcite by self-assembly and intercalation, thereby improving the connection strength between the nanocellulose and the hydrotalcite, and then improving the bonding strength between the polystyrene particles and the hydrotalcite, that is, the hydrotalcite can fully disperse the polystyrene particles.

[0103] 5. By comparing Examples 7-9 with Example 3, it can be found that the fire resistance and mechanical properties of the gypsum mortar prepared in Examples 7-9 are improved, which means that in the present application, redispersible latex powder is used to wrap the polystyrene particles, forming a redispersible latex shell outside the polystyrene particles, making the polystyrene particles hydrophilic, and improving the dispersion effect of the polystyrene particles in the gypsum mortar. As the mixing time increases, the waterproof powder can be gradually released, and the aminosilane, alkoxysilane and PVA in the waterproof powder can form an interpenetrating network with silicone gel, aluminum gel and hydrated calcium sulfoaluminate, further improving the bonding effect between the polystyrene particles and cement, and effectively improving the strength of the gypsum mortar.

[0104] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A high-strength fire-resistant gypsum mortar, characterized in that: The following materials are included in parts by weight: 60-80 parts of gypsum; 20-30 parts of cement; Aggregate 10-20 parts; 5-10 parts of filler; 3-5 parts of admixture; The filler includes glass microspheres, polyphenyl particles and redispersible latex powder, and the filler also includes layered hydrotalcite; The layered hydrotalcite is a layered hydrotalcite modified by a modifier, and the modifier includes nanocellulose; The nanocellulose includes modified nanocellulose modified by stearyl chloride.

2. A high-strength fire-resistant gypsum mortar according to claim 1, characterized in that: The modified nanocellulose is prepared as follows: nanocellulose, N,N-dimethylacetamide and pyridine are mixed, stearoyl chloride is added, stirred for reaction to obtain a reaction product, the reaction product is dispersed in ethanol, centrifuged, the precipitate is retained, washed, and dried to obtain the modified nanocellulose.

3. The high-strength fire-resistant gypsum mortar according to claim 1, characterized in that: The nanocellulose also includes grafted nanocellulose, on which cyclodextrin is grafted.

4. The high-strength fire-resistant gypsum mortar according to claim 1, characterized in that: The polyphenylene particles are loaded with waterproof powder.

5. A high-strength fire-resistant gypsum mortar according to claim 4, characterized in that: The polyphenylene particles are coated with redispersible latex powder.

6. A high-strength fire-resistant gypsum mortar according to claim 5, characterized in that: The polystyrene particles are prepared as follows: the polystyrene particles are immersed in a waterproof powder finishing liquid, stirred and mixed, filtered, and dried to obtain loaded polystyrene particles, and a redispersible latex liquid is sprayed on the surface of the loaded polystyrene particles to obtain modified polystyrene particles.

7. The high-strength fire-resistant gypsum mortar according to claim 1, characterized in that: The admixture includes a water reducer and zinc borate, and the water reducer includes a polycarboxylate water reducer.

8. The method for preparing a high-strength fire-resistant gypsum mortar according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1. Raw material preparation: Take gypsum, cement, filler, aggregate, admixture and water respectively by weight; S2. Preparation of mortar: Stir and mix the filler, aggregate and admixture, add gypsum and cement and mix evenly, then add water and continue stirring to prepare gypsum mortar.

Citation Information

Patent Citations

  • Inorganic insulation mortar for building lightweight insulation brick

    CN103641386A

  • Gypsum-based composite lightweight thermal-insulation mortar and preparation method thereof

    CN109942267A

  • Phosphomolybdic acid intercalated hydrotalcite-like light foam heat insulation material and preparation method thereof

    CN110669246A